W9 Mental health simulation – how it works and why is it important for you?An introduction to mental health simulation with interactive scenario demonstration. (November 2018) - Pathan, James; Williams, Leonie
Abstract : All participants welcome including; simulation faculty, technicians, managers and education planners. Background: Mental health simulation is increasing being used to train professionals from multi-disciplinary teams across the wider health and social care system and not just in hospital based settings. These areas include primary care, pharmacy, schools, community services and general public realm. A range of simulation courses developed at Maudsley Simulation are currently being delivered across south London not just in highly resourced simulation centres, but also in local settings such as GP practices and health centre training rooms. The types of professionals being trained on these multi-disciplinary courses include; GPs, Specialist Nurses, Health Visitors, Social Workers, School Nurses, Occupational Therapists, Pharmacist and Pharmacy Counter Assistants, GP Practice Managers and Receptionists, Administrators and other non-clinical workforce. Evaluation data has shown that staff attending these courses have reported increased understanding, confidence and attitudes towards a cross-system approach to delivering high quality care. Learning outcomes: Participants will have an increased understanding of: the value of mental health simulation in all areas health and social care. how multi–disciplinary simulation and multi–agency simulation can support a 'whole system' approach to patient care. what a typical mental simulation scenario looks like, how it works and how it is typically debriefed. how mental health simulation using actors can be supported technically in relatively simple environments. the value of incorporating mental health simulation scenarios into your area of work. Structure of workshop: Participants will be given a short overview of mental health simulation and where it is currently being successfully employed. This will include the use of video and power point presentation to show examples of various simulation courses being delivered with cross-system learning objectives including evaluation data from participant reporting. Some participants attending will have the opportunity to partake in an high fidelity simulation scenario taken from one of Maudsley Simulation's courses, others will also take part in the live scenario through taking part in active observation and debrief. The workshop hopes to demonstrate a complete mental health simulation scenario with direct participation from workshop attendees. The session aims to show the full simulated learning cycle experience from one scenario and debrief. The session will be delivered by simulation based education trained actors (simulated patients), facilitators and deployed using a portable simulation solution developed by in-house at Maudsley Simulation. Educational methods to be used: Simulation based education Interactive group activity Video and didactic presentation.